Treinamento cognitivo em escolares de diferentes níveis intelectuais - Marcela Mansur Alves (2012)
The present study have as main objectives to verify the effectiveness of working memory program to improve intelligence of Brazilian children of different intellectual levels, and to investigate the relationship between EEG parameters and individual differences in intelligence. In order to achieve the first objective, 53 children from the sixth year of primary education (M = 11.17 years, SD = 0.376) took part in this study. They were randomly assigned to compose the experimental group/GE (n = 26) and control group/GC (n = 27). Each group was divided into three subgroups according to the IQ level: high (IQ above 120), average (IQ in the range 95-110 points) and low (IQ between 70 and 85 points). At pretest, children were assessed with measures of cognitive and academic performance. There were two posttests, using the same instruments of the pretest, one of them took place one month after the last training session and the other four months after the end of training. Three tasks of working memory were used for training. The children received the intervention at the school twice a week for 10 weeks at the most. No significant differences were found between the training and control group at post-test performed one month after training and, also, four months after that, for any measures of cognitive and academic performance. However, for the low IQ group, the difference (d index) between GC and GE on the Raven test which was favorable to GC prior to the training (3.75 IQ points) came to be favorable to GE immediately after training (d = -0.47 or 7.05 IQ points). The results are partially supported in the literature and point to the difficulty in finding genuine intellectual change with intervention programs of short duration. Nevertheless, studies with a larger sample size, younger participants and longer duration of training are required to verify the generality of these findings. Regarding the second objective, thirteen children with a mean age of 11 years (four of high IQ and 9 of average IQ) had their EEG collected during the performance of a working memory task and during rest. Analyses were performed in order to calculate the correlation between the percentage of event-related desynchronization and intellectual level of the child and provide evidence about the phenomenon of neuronal efficiency. The results point to a greater percentage of event-related desynchronization (greater neural activity) for children of high IQ, especially in the frontal and parietal lobes, although the analysis did not reach statistical significance. The results can be explained if we consider the existence of moderating variables of the phenomenon of neuronal efficiency, such as sex, difficulty of the task used, and the reference and activity interval chosen.